2017
DOI: 10.9734/ijtdh/2017/31448
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicines Used in the Treatment of Typhoid in the Ga East Municipality of Ghana

Abstract: In Ghana, majority of the people patronize herbal medicines for the treatment of both chronic and acute ailments as well as infectious and non-infectious diseases. As such, the use of herbs as medicines in the treatment of enteric (typhoid) fever is very widespread. Aims: This study therefore investigates anti-typhoidal herbal medicinal formulations that are for sale on the Ghanaian market with regards to the contents on the product labels and assesses the various active plant components in the light of docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
4
3
0
Order By: Relevance
“…The others were Nauclea latifolia (55.6%), Enantia chlorantia (44.4%), Sphenocentrum jollyanum, and Citrus aurantifolia (38.9%) (Figure 3). This finding agrees with that of Bekoe et al (2017), who demonstrated the aforementioned as the most recurring plant active constituents of herbal medicines in Ghana. It seems possible that this may be because most herbal preparations were developed for multiple indications.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The others were Nauclea latifolia (55.6%), Enantia chlorantia (44.4%), Sphenocentrum jollyanum, and Citrus aurantifolia (38.9%) (Figure 3). This finding agrees with that of Bekoe et al (2017), who demonstrated the aforementioned as the most recurring plant active constituents of herbal medicines in Ghana. It seems possible that this may be because most herbal preparations were developed for multiple indications.…”
Section: Discussionsupporting
confidence: 92%
“…It is therefore obvious why most of these herbal preparations are multi-indicated, as further analysis revealed that all the antimalarial herbal preparations contain more than one plant species as their active component, with 66.7% comprising between 1 and 5 plant species as the active ingredients, while 16.7% contain between 5 and 10 and more than 10 active ingredients, respectively (Table 1). This result is consistent with that of Bekoe et al (2017). Of these, Azadirachta indica (83.3%) was the most common active component of the surveyed herbal preparations.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations